GDF15 Interference Regulates Proliferation, Inflammation, and Autophagy of Lipopolysaccharide-induced Mesangial Cells by Inhibiting PI3K/ AKT/mTOR Signaling - Chen, Zhen; Gao, Liping; Li, Cailing; Sun, Wenzhu (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
>Background: Chronic glomerulonephritis (CGN) is a primary glomerular disease. As a circulating protein, growth and differentiation factor 15 (GDF15) participates in a variety of biological processes. Objective: We aimed to investigate the role of GDF15 in CGN. Methods: HBZY-1 cells were induced by lipopolysaccharide (LPS). Cell viability was detected using a cell counting kit-8 (CCK-8) assay, and a western blot was applied for the detection of GDF15 protein expression. After GDF15 silencing, cell proliferation was evaluated by CCK-8 assay and 5-ethynyl-2'-deoxyuridine (EDU) staining. Enzyme-linked immunosorbent assay (ELISA) kits were used to detect the levels of inflammatory cytokines. Autophagy was assessed by GFP-LC3B assay. Besides, the expression of NF-ΚB signaling-, autophagy- (LC3II/I, Beclin l and p62) and phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mechanistic target of rapamycin (mTOR) signaling-related proteins were measured by western blot. Afterwards, PI3K agonist 740Y-P was used to clarify whether GDF15 affected LPS-induced HBZY-1 cells via PI3K/AKT/mTOR signaling. Results: LPS induction increased cell viability and elevated GDF15 expression in HBZY-1 cells. After GDF15 expression depletion, the increased proliferation of LPS-induced HBZY-1 cells was decreased. Additionally, GDF15 knockdown suppressed the release of inflammatory factors in LPS-induced HBZY-1 cells and activated autophagy. Moreover, the PI3K/AKT/ mTOR signal was evidenced to be activated by GDF15 deficiency. The further addition of 740Y-P reversed the impacts of GDF15 deficiency on the proliferation, inflammation, and autophagy of LPS-induced HBZY-1. Conclusion: Collectively, GDF15 downregulation could protect against CGN via blocking PI3K/AKT/mTOR signaling.
Keywords: Chronic glomerulonephritis